Theater for Language Teaching and Learning: The E Theater, a Holistic Methodology (2018)
This article reports the findings of a qualitative study based on a long-term application of a theater content-based methodology for L2 learning, supported by professionals in theater and in foreign languages, in The E Theater: an English as a foreign language theater interdisciplinary group at Universidad Nacional de Colombia that has been active since 2008. The data were collected through a longitudinal semi-structured survey, interviews of the participants of the event, and a focus group. As a result, participants stated lowering their affective filter and benefits in their production and comprehension of L2 skills, their intercultural competence, and their cognitive processing of the language derived from the methodology carried out.